Farmer Training and coaching has increased the knowledge and implementation of over 1000 cocoa farmers in Climate Smart Cocoa practices in Ghana. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Field surveys have shown that the 1113 farmers coached in the climate-smart cocoa have implemented practices in their farms in the coping and adjustment zones in Ghana. Each farmer has implemented at least 2 climate-smart cocoa recommendations in the establishment and management of their cocoa farm. Farmers who Planted new cocoa observed a 30-35% increase in the survival rate of transplanted cocoa seedlings. Matured cocoa farms after using the CSC recommendation also recorded a 10- 30 % increase in yield